Simulation of anti-reflective TiO2/SiO2 coating for silicon photovoltaic application by ray tracing / Imran Al-Haqeem Jaffar, Siti Hajar Mohmad Salleh, Mohd Zaki Mohd Yusoff - Jaffar, Imran Al Haqeem; Mohmad Salleh, Siti Hajar; Mohd Yusoff, Mohd Zaki (Universiti Teknologi MARA Shah Alam, 2023)
In solar systems, anti-reflective coatings are used to reduce reflection and increase efficiency. However, the front surface on the solar cells alone is not effective because most of the light from the sun is reflected and very less energy absorption into the solar cells occur. An anti-reflective coating (ARC) of a sufficient thickness can greatly reduce front surface reflectance. Nanoscale surface texturing, on the other hand, can efficiently capture a higher ratio of incident light to boost optical absorption. In this study, the light trapping scheme within the wavelength of 300 to 1200 nm was used to improve the overall efficiency of silicon solar cells. A thin layer of TiO2 and SiO2 anti-reflective coating with different thicknesses was stacked alternatingly due to their different refractive index with TiO2 having a high refractive index and SiO2 with a low refractive index. Solar irradiance spectrum AM1.5G at normal incidence was used in this present work. For the ray-tracing simulation, the front planar with multilayer ARC with different thicknesses were investigated to obtain the optimum value for optical properties and current density. All the four combination arrangements of SiO2 and TiO2 were evaluated and the maximum potential photocurrent density (Jmax) was calculated. The Jmax value of thin crystalline silicon, c-Si (without ARC) was 24.93 mA/cm2 and increased to 30.28 mA/cm2 when ARC was used on the front surface. This represents an increasing of 21.46 % enhancement compared to the Jmax of the c-Si reference.